Comparative evaluation of displacement and stress distribution pattern during mandibular arch distalization with extra and inter-radicular mini-implants: a three-dimensional finite element study - Amit MAHESHWARI; Dhruv Nilesh CHAWDA; Ashish KUSHWAH; Rajesh Kumar AGARWAL; Amesh Kr GOLWARA; Prateek Bhushan DIXIT (Dental Press Editora, 2023)
ABSTRACT Objective: To compare the initial stress distribution and displacement on mandibular dentition using extra and inter-radicular mini-implants for arch distalization, by means of finite element analysis. Methods: For this study, two finite element models of the mandible were designed. The models consisted of periodontal ligament (PDL) and alveolar bone of all teeth until second molars. In the Case 1, bilateral extra-radicular buccal-shelf stainless steel mini-implants (10.0-mm length; 2.0-mm diameter) were placed between first and second permanent molars. In the Case 2, bilateral inter-radicular stainless steel mini-implants (10.0-mm length; 1.5-mm diameter) were placed between second premolar and first permanent molar. Power hook was attached between canine and first premolar at a fixed height of 8mm. In the two cases, 200g of distalization force was applied. ANSYS v. 12.1 software was used to analyze and compare von Mises stress and displacement in the mandibular dentition, PDL and bone. Results: Higher stresses were observed in mandibular dentition with the inter-radicular implant system. The amount of von Mises stress was higher for cortical bone (85.66MPa) and cancellous bone (3.64MPa) in Case 2, in comparison to cortical bone (41.93MPa) and cancellous bone (3.43MPa) in Case 1. The amount of arch distalization was higher for mandible in Case 1 (0.028mm), in comparison to Case 2 (0.026mm). Conclusion: Both systems were clinically safe, but extra-radicular implants showed more effective and controlled distalization pattern, in comparison to inter-radicular implants, in Class III malocclusion treatment.